Pengembangan Model Wakaf Produktif untuk Pembiayaan Haji dan Umrah Berkelanjutan di Indonesia - Rara Genta Munggarani Basri; Syarifah Gustiawati Mukri; Naufal Dwi Lisardi (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2026)
This study aims to develop a sustainable productive waqf model for Hajj and Umrah financing through the integration of Islamic social finance and sharia-compliant investment mechanisms. Previous studies have primarily focused on the role of productive waqf in education, healthcare, and economic empowerment, while its application to Hajj and Umrah financing remains limited. This study uses a qualitative approach to the method of literature studies. Secondary data were obtained from scientific literature and regulatory documents related to waqf, Hajj, and umrah, and then analyzed using content analysis techniques to develop productive waqf models. The findings indicate that productive waqf can serve as a sustainable financing source through a professionally managed endowment fund scheme. The proposed model involves wakif, nazhir, and Islamic financial institutions in generating investment returns that can be allocated for Hajj and umrah subsidies and support. This model contributes to expanding access to pilgrimage financing in a more inclusive, equitable, and sustainable manner.